Albumin promotes the progression of fibroblasts through late G1 into S-phase in the absence of growth factors. Issue 17 (1st September 2020) - Uddin, Sharmeen; Melnyk, Nataliya; Foster, David A.
ABSTRACT: G1 cell cycle progression is controlled largely by growth factors in early G1 indicating that it is appropriate to divide and by nutrients in late G1 indicating sufficient raw material for cell division. We previously mapped a late G1 cell cycle checkpoint for lipids upstream from a mammalian target of rapamycin complex 1 (mTORC1)-mediated checkpoint and downstream from a mid-G1 checkpoint known as the Restriction point. We therefore investigated a role for lipids in progression through late G1 into S-phase. Quiescent BJ-hTERT human fibroblasts were primed with 10% fetal bovine serum (FBS) for 3.5 h at which time, cells were treated with a mixture of lipids and carrier bovine serum albumin (BSA) along with [ 3 H]-thymidine deoxyribose ([ 3 H]-TdR) to monitor progression into S-phase. Surprisingly, BSA by itself was more effective than FBS in promoting progression to S-phase – the lipids had no impact on progression. While insulin strongly stimulated mTORC1 activity, it did not impact on [ 3 H]-TdR incorporation. Although BSA modestly elevated mTORC1 activity, rapamycin strongly inhibited BSA-induced progression to S-phase. BSA treatment promoted mitosis, but not progression through a second G1 . Thus, after priming quiescent cells with FBS, albumin was sufficient to promote progression into S-phase. The BSA was not simply a source of amino acids in that amino acids were present in the culture media. We propose that the presence of albumin – the most abundant protein in serum – reflects a broader availability of essential amino acids needed for cell growth.